Penanganan Pertama Trauma pada Gigi Dewasa Disertai Perawatan Gigi Sederhana Kepada Warga Kelurahan Kembangan Selatan Jakarta Barat - Ariwibowo, Taufiq; Reza Tanaka, Ricky; Mahardika Wibowo, Pramana; Kadek Resi Brahmani, Luh; Juliana; Edwina Halim, Heidi; Wangidjaja, Bryan; Wulansari, Selviana; Elsa Prahasti, Anastasia; Prijanti Dwisaptarini, Ade; Shelvannia Haryanto, Viola (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
Dental trauma is a common condition caused by physical injury to the teeth and surrounding oral structures, often resulting from accidents, falls, or sports activities. Immediate management is crucial to prevent complications such as pulp necrosis, infection, or tooth loss, which may negatively affect mastication, aesthetics, and self-confidence. This Community Partnership Program (PKM) aims to increase public awareness and knowledge of first aid for dental trauma in adults through educational counseling and basic dental treatment. The program targets residents of Kembangan Selatan, West Jakarta, with 75 participants. Activities include interactive education sessions, demonstrations, and simple dental treatments such as fillings, pre-medication, initial endodontic care, and referrals. The expected outcomes include improved understanding of dental trauma management, enhanced preventive behavior, and the creation of intellectual property in the form of educational poster. This initiative demonstrates the commitment of Universitas Trisakti’s Faculty of Dentistry to promote oral health and empower communities in managing dental emergencies effectively.